ASUPAN ZAT GIZI, STATUS GIZI, DAN STATUS ANEMIA PADA REMAJA LAKI-LAKI PENGGUNA NARKOBA DI LEMBAGA PEMASYARAKATAN ANAK PRIA TANGERANG - Wahyuningsih, Utami; Khomsan, Ali; Ekawidyani, Karina Rahmadia (Jurnal Gizi dan Pangan, 2014)
The objective of this study was to analyze the intake of energy and nutrients, nutritional status, and anemia status in adolescent boys with drug abuse at boys penitentiary class IIA Tangerang. This study used cross sectional design. Subjects of this study were adolescent boys with drug addiction. Sampling method used was purposive sampling and the number of subjects was 40 people. Descriptive analysis showed energy (35.0%) and protein (27.5%) adequacy level were categorized as severe deficit. Mean energy from food provided by the penintentiary hadn’t met subjects’ daily requirement while mean protein had met subjects’ daily requirement. Iron adequacy level was categorized as adequate (82.5%) and vitamin C adequacy level was categorized as inadequate (100.0%). Most subjects had normal nutritional status (85.0%) and anemia (57.5%).